Island Sign Predicts Hematoma Expansion and Poor Outcome After Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis - Wei, Yufei; Zhu, Guangming; Gao, Yonghong; Chang, Jingling; Zhang, Hua; Liu, Nan; Tian, Chao; Jiang, Ping; Gao, Ying (Frontiers in Neurology, 2020)
Background: Early hematoma expansion (HE) occurs in patients with intracerebral hemorrhage (ICH) within the first few hours from ICH onset. HE has been considered as an independent predictor of poor clinical outcome and mortality after ICH. Island sign (IS) on the noncontrast computed tomography (NCCT) appears to increase the rate of detection of HE. However, there is insufficient evidence to declare that IS is an independent predictor for ICH patients prognosis and classification. Objectives: To investigate whether island sign on NCCT could predict hematoma expansion and functional outcome following ICH. Methods: Major databases were systematically searched, including PubMed, Embase, Cochrane library, and the Chinese database (CNKI, VIP, and Wanfang databases). Studies about the associations between IS and HE or IS and clinical outcome were included. The pooled result used the odds ratio (OR) with a 95% confidence interval (CI) as effect size. Heterogeneity and publication bias were assessed. Subgroup analysis and meta-regression were applied to detect potential factors of heterogeneity. Results: 11 studies with 4310 patients were included in the final analysis. The average incidence rate of island sign and hematoma expansion were 21.58% and 33%, respectively. The ideal timing for assessing HE was also not uniform or standardized. We separately performed two meta-analyses. Firstly, ten studies were included to estimate the association between IS and HE. The pooled OR was statistically significant (OR, 7.61; 95% CI, 3.10-18.67; P <0.001). Secondly, four studies were included in the meta-analysis, and the pooled result showed that IS had a significantly positive relationship with poor outcome (OR, 3.83, 95% CI, 2.51-5.85, P <0.001). Conclusions: This meta-analysis showed that NCCT island sign is of great importance and value for evaluation of HE and poor outcome in patients with ICH. Future studies should focus on developing consensus guidelines, and more studies with large sample size and longitudinal design are needed to validate the conclusions.